WORK STUDY (MOTION AND TIME STUDY) IN THE GENERAL ESTABLISHMENT FOR LEATHER INDUSTRIES (AS AN APPLIED MODEL) - Jawad Najy, Raqeyah (IJRDO - Journal of Business Management, 2023)
The study of work has a direct relationship to productivity and is usually used to increase the amount of production with a limited amount of resources without resorting to additional investments except in some cases and on a small scale. Studying work as one of the methods that lead to raising productivity, as the principles of work study were applied to one of the industrial facilities, specifically in (the leather shoes factory in the eastern Karadat) - Factory No. (1) of the General Establishment for Leather Industries, and a study of movement and time was conducted on a linear basis Separation and sewing of shoe model (701) women’s textile shoes, and there were several savings and differences between the current method of work and the proposed method. Removing bottlenecks and not removing the basic processes for manufacturing the product with the most important recommendations.